2018
DOI: 10.1039/c8dt04409k
|View full text |Cite
|
Sign up to set email alerts
|

Redox-state dependent activation of silanes and ammonia with reverse polarity (PCcarbeneP)Ni complexes: electrophilic vs. nucleophilic carbenes

Abstract: A rigidified PCalkylP ligand allowed for the synthesis and characterization of cationic and radical PCCarbeneP nickel complexes in which the carbene anchor of the pincer framework is electrophilic rather than nucleophilic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 98 publications
1
29
0
Order By: Relevance
“…Given that both Pt II and Pt IV salts and complexes are effective π‐acid catalysts, we sought to isolate well‐defined examples of cationic Pt II and Pt IV carbene complexes to probe the bonding in these important species. Hypothesizing that a strong ligand chelate may be able to support these species, we employed the rigid, 10,10‐dimethyl‐9,10‐dihydroanthracene‐derived PCP ligand framework L 1 , which is competent in the stabilization of analogous nickel(II) complexes . For comparison, an isostructural Pd II species was also prepared and it was shown that the Pt−C bonds are indeed more stable due to stronger π bonding, attributable to relativistic effects.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Given that both Pt II and Pt IV salts and complexes are effective π‐acid catalysts, we sought to isolate well‐defined examples of cationic Pt II and Pt IV carbene complexes to probe the bonding in these important species. Hypothesizing that a strong ligand chelate may be able to support these species, we employed the rigid, 10,10‐dimethyl‐9,10‐dihydroanthracene‐derived PCP ligand framework L 1 , which is competent in the stabilization of analogous nickel(II) complexes . For comparison, an isostructural Pd II species was also prepared and it was shown that the Pt−C bonds are indeed more stable due to stronger π bonding, attributable to relativistic effects.…”
Section: Figurementioning
confidence: 99%
“…The 13 C{ 1 H} NMR spectra contain distinct singlets at 257.7 ppm for 2 Pd and 229.7 ppm (with observable 195 Pt satellites, J C‐Pt =1118 Hz) for 2 Pt . The carbene carbon in the isostructural Ni complex 2 Ni appears at 250.8 ppm …”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations